Experimental Demonstration and Characterization of a Non-Mode Selective (De)Multiplexer Using Multi-Plane Light Converter (MPLC) - Shree R. Thapa; Seth Smith-Dryden; Zheyuan Zhu; Shuo S. Pang; Guifang Li (IEEE Photonics Journal)
We experimentally demonstrate the use of a multi-plane light converter (MPLC) as a non-mode selective (de)multiplexer for converting Hermite-Gaussian (HG) modes into a Hadamard matrix of fundamental Gaussian spots and vice versa. We interferometrically measure and characterize the complex output of the device and successfully demonstrate the conversion between HG modes and Hadamard matrices of Gaussian spots. The MPLC non-mode selective (de)multiplexers can be useful for versatile control of spatial properties of light beams with potential applications in beam shaping, coherent beam combining, and wavefront synthesis.